Green Synthesis and Evaluation of Dimocarpus longan Leaves Extract Based Chitosan Nanoparticles against Periodontitis Triggering Bacteria - Fuloria, N.K.; Ko, M.Y.; Rui, C.S.; Hang, C.Z.; Karupiah, S.; Paliwal, N.; Kumari, U.; Gupta, K.; Sathasivam, K.; Fuloria, S. (Asian Journal of Chemistry, 2020)
Present study was intended to synthesize and evaluate the Dimocarpus longan leaves aqueous extract (DLLAE) based chitosan nanoparticles (CSNPs) against periodontitis triggering bacteria. In present study the DLLAE was prepared by extracting D. Longan leaves in distilled water using decoction method. The prepared DLLAE was subjected to phytochemical investigations, total phenolic content, total flavonoid content study and CSNPs synthesis. The CSNPs were characterized (using UV-visible, FT-IR, SEM, FESEM, XRD and EDX) and evaluated for their potential against periodontitis triggering bacteria (using agar well diffusion method). The phytochemical investigations over DLLAE exhibited presence of monosaccharides, reducing sugars, proteins, steroids, anthraquinones and coumarins glycosides, flavonoids, alkaloids, organic acid, tannic and phenolic compounds. The CSNPs were formed using DLLAE when the colour changed from white to pale brown. Absorbance of the CSNPs was in the desired range (201-310 nm). The optimization study revealed 1% acetic acid, 1% sodium alginate, 2 mg/mL chitosan, pH 5.8 and 1 mL DLLAE as the standard requirement for CSNPs synthesis using DLLAE. The CSNPs characterization data of FT-IR exhibited shifted bands. The FESEM revealed that the synthesized CSNPs were spherical in shape and their size ranged from 74.66 to 94.07 nm. The XRD data showed peaks at 2θ values of 22.28º, 25.19º, 34.72º, 40.0º, 71.16º and 73.0º. The average size for CSNPs was between 30.11-62.98 nm. The EDX spectrum revealed signal for carbon (76.17%), oxygen (22.14%) and sodium (1.53%) which confirmed formation of CSNPs. The antibacterial activity revealed high inhibitory potential of green CSNPs against S. aureus. Present studies establish that CSNPs biosynthesis using D. longan leaves aqueous extract is an efficient method and the biosynthesized CSNPs possess high antibacterial potential against S. aureus (bacteria that triggers periodontitis).